LANGUAGE STYLE, FUNCTIONS, AND VALUES IN PALEBOHU ORAL POETRY AT A TRADITIONAL WEDDING CEREMONY IN GORONTALO - Dakia N. Djou; Asna Ntelu (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
Palebohu is a form of oral poetry that is performed in a traditional wedding ceremony in Gorontalo. Palebohu also uses various styles of language that are actualized in their verses that describe the characteristics and norms upheld by the people of Gorontalo. Therefore, this study aims to describe the language style, function, and values contained in palebohu in traditional wedding ceremonies in Gorontalo Province. The data used are palebohu array quotes that describe palebohu's language style, functions, and values. The results of the study show that (1) palebohu employs: (a) alliteration, (b) assonance, (c) repetition, (d) euphemism, and (e) parallelism language styles; (2) palebohu functions: (a) as a medium for delivering advice which includes advice on navigating the household, advice on social life and the behavior desired by the community, and advice on establishing good relationships with parents, in-laws, and siblings ; (b) as a medium for conveying religious teachings; and (c) as a form of custom; (3) the values in palebohu oral poetry are: (a) moral, (b) social, (c) religious, (d) cultural, and (e) aesthetic.